KRIPIK AYAM BUMBU BALI SEBAGAI ALTERNATIF USAHA BAGI IBU RUMAH TANGGA - Suryandari, Ni Nyoman Ayu; Yuliastuti, Ida Ayu Nyoman; Primadewi, Siluh Putu Natha (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
Chicken Chips is a traditional snack cultivated by people from various circles. It's tasty to make chicken chips can be enjoyed as a snack when casual or side dishes when eating. But along with the many parties who like, chicken chips can now be a business opportunity with a turnover of millions of dollars. This opportunity is utilized by Mrs. Putu Yuliana (43) by establishing a business of making chicken chips "Mesari". Chicken Chips excellence Mrs. Yuliana when compared to other similar products is more tasty taste of chicken chips taste. At first glance, the chicken chips creations of Mother Yuliana does look different when compared with chicken chips mostly with larger and larger shapes, larger packaging and thicker plastic so that makes the chicken chips look more neat than other chicken chips. This program is interesting to be implemented because the partners have the potential to grow but the business is still home industry that still use the machine and manual processing. Activities in this program involves two aspects, namely aspects of production and management aspects. The results that have been achieved in this program are: Aspects of production include 1). Supply of 1 grinding machine, 2). Procurement of 1 blender, 3). Procurement of 1 machine oil slicer (spinner), 4). Procurement of 2 packets of hand slippers. From the aspect of management is: 1). Counseling and guidance on simple bookkeeping, 2). Extension of new product innovation. In addition, the outcome of this program is 1). Draft scientific publications on journals, 2). Teaching materials, 3). Increase in quantity and quality of product with the addition of machine, 4). Improved understanding of simple bookkeeping, and 5). Increased revenue.